Analisis Pengendalian Kualitas Produk Seat Frame Front Cushion Menggunakan Metode Quality Control Circle (QCC) pada PT TBA - Muhamad Rizki Budiansyah; Agus Suwarno; Annisa Syahliantina (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
PT TBA as a manufacturing company in the automotive industry faces quality problems in the form of defects in the wrong assembly arm in the Inner Left Normal process of Seat Frame Front Cushion products in the EFC Line Adjuster. Based on data for the March-May 2025 period, the average defect reaches 1.3 pcs per month and has the most dominant cost impact compared to other types of defects, with a potential material loss of up to IDR 6,236,708 per year. This study aims to identify the root cause of the problem and reduce the number of defects to zero defects through the application of the Quality Control Circle (QCC) method with an eight-step approach based on the PDCA cycle. The results of the analysis showed that the main cause came from the incompatibility of the arm rack design which allowed the mixing of right and left components, uncontrolled part picking methods, and the lack of optimal error prevention system (poka-yoke) on the machine. Improvement actions are carried out through modification of the rack design following the shape of the arm, the installation of a lever and gravity-based mechanical cover system, and the integration of sensors and poka-yoke systems in the process area. After all stages of QCC were implemented, defects were successfully reduced to 0 pcs per month consistently from August to October 2025 or a decrease of 100%. The impact of the improvement not only improves the quality aspect, but also eliminates the potential cost loss to Rp 0, without affecting the aspects of safety, delivery, and employee morale. These results prove that QCC is effective as a sustainable quality control approach in the automotive industry.